Feasibility of manufacturing of Al2O3–Mo HTCC by hybrid additive process. Issue 11 (1st June 2022) - Bernard, Mégane; Pateloup, Vincent; Passerieux, Damien; Cros, Dominique; Madrangeas, Valérie; Chartier, Thierry
Abstract: Additive manufacturing processes make it possible to produce increasingly complex 3D parts. In addition, these numerical processes can be usefully used to manufacture ceramic/metal parts of high dimensional resolution with thermal, electrical and electronic properties of interest for applications in the field of power electronics. In this context, a hybrid additive machine was developed to manufacture ceramic/metal parts. This machine consists in the combination of two additive manufacturing processes: stereolithography and robocasting. Using this hybrid process, the feasibility of HTCC components has been demonstrated by building dielectric alumina by stereolithography and molybdenum conductive network by robocasting. Molybdenum-based metallic formulation adapted to the process and allowing to obtain a high conductive metallic network has been developed. The co-debinding and co-sintering cycles have been optimized to minimize the content of residual carbon and to prevent the oxidation of molybdenum. The alumina/molybdenum interface has also been observed to conclude about a possible delamination between these two materials with different thermal expansion coefficients (CTE). Sintered HTCC parts have been characterized in the domain of hyperfrequency. The frequency responses deviate from the simulation due to a lack of dimensional accuracy of the metallic network.